Anti-inflammatory effects of 4′-demethylnobiletin, a major metabolite of nobiletin. (December 2015) - Wu, Xian; Song, Mingyue; Rakariyatham, Kanyasiri; Zheng, Jinkai; Guo, Shanshan; Tang, Zhonghai; Zhou, Shuangde; Xiao, Hang
Highlights: 4′-Demethylnobiletin (4DN) dose-dependently inhibited lipopolysaccharide (LPS)-induced nitric oxide production in macrophages. 4DN inhibited reduced LPS-induced expression of pro-inflammatory proteins, namely, iNOS, COX-2, PGE2, IL-1β and IL-6. 4DN inhibited LPS-induced nuclear translocation of NF-κB and AP-1. 4DN activated transcription factor Nrf2 and its dependent genes, including HO-1 and NQO1. Abstract: Nobiletin, a citrus flavonoid, has been associated with various beneficial biological activities. 4′-Demethylnobiletin (4DN) is a major metabolite of nobiletin, and its tissue level was found to be much higher than that of nobiletin after oral administration of nobiletin in mice. Anti-inflammatory effects of 4DN were studied in lipopolysaccharide (LPS)-treated RAW 264.7 macrophages. The results showed 4DN not only dose-dependently inhibited LPS-induced nitric oxide production, but also significantly reduced expression of pro-inflammatory mediators, namely PGE2, IL-1β and IL-6. 4DN potently suppressed the expression of iNOS and COX-2 at both protein and mRNA levels. 4DN also inhibited nuclear translocation of NF-κB and AP-1. Furthermore, we demonstrated that 4DN activated transcription factor Nrf2 and its dependent genes including HO-1 and NQO1 whose expression may contribute to anti-inflammatory effects. The results demonstrated anti-inflammatory effects of 4DN and provided a scientific basis for using nobiletin as a nutraceutical to inhibit inflammation-driven diseases.